Newly designed dual-mode electrochemical sensor onto a single polydimethylsiloxane-based chip - Maximiano, Elizabete Maria; Sequinel, Thiago; Martins, Cauê Alves; Angnes, Lucio; Gonçalves Trindade, Magno Aparecido [UNESP] (Elsevier, 2021)
Here we present a planar polydimethylsiloxane (PDMS)-based millifluidic device in which the channel (at a serpentine-shape) and a new design of electrochemical sensor (dual-mode detection) are assembled into a single chip. The platform makes use of a fully integrated reservoir to place the reference electrode, separating it from the flowing stream. The device was properly characterized aiming to evaluate the influences of channel geometries and diameters, and the electrochemical properties were improved compared with the classical reference electrode configuration. To investigate the applicability of the proposed millifluidic device, amperometric detection was used for the analysis of tap and lake water as well as groundwater samples to determine salicylic acid — selected as a model analyte. Our experimental results have demonstrated a successful prospect as amperometric detection in PDMS-based chip and showed high tolerance to disturbance by external action provided in the use of electronic micropipette and no surface inactivation from sample-interference.
Keywords: Dual-mode sensor; Integrated flow cell; Newly designed electroanalytical chip; Salicylic acid